Foundations of radar synthesis theory of phantom objects formation in SAR images - Volodymyr Pavlikov; Simeon Zhyla; Pavlo Pozdniakov; Denys Kolesnikov; Hlib Cherepnin; Olexandr Shmatko; Oleksii Odokiienko; Pavlo Malashta; Eduard Tserne (Радіоелектронні і комп'ютерні системи)
The primary research area is developing a theory of false object formation in aerospace radar images. This process involves adding the spatial and temporal trajectory signals of the object information features that are absent on the underlying surface irradiated by an aerospace carrier. The goal of this study is to determine the general concepts of the design and application of radar image phantomization radars. The research is aimed at solving the following tasks: to describe the general concept of phantomization radar (PhR) design and application; to formulate the hypotheses underlying the theory and outline the range of issues to be solved; to determine the general structure of PhR; to develop mathematical models of the laws of distance change in the system “phantom image generator – remote sensing radio system”; to determine the size limitations of the area where phantom replacement of real radio images can be provided following the viewing mode of the underlying surface from satellites. The solution to these tasks is based on the methods of the remote sensing system synthesis theory, radiophysics, coherent image formation, functional analysis, synthesis, and processing of spatiotemporal signals. The following results were obtained: 1) the structure of the PhR is defined, which includes a receiver, a bank of SAR signal models, a bank of object models to be injected into the PhR signal, and a transmitter; 2) the parameters of the received SAR sensing signal that need to be estimated in the PhR receiver are determined; 3) the geometry of interaction in the “SAR-PhR” system is described, which allowed us to determine an expression for estimating the distance between SAR and PhR, as well as to estimate the distance-related parameters, such as signal delay time and characteristics of sensing signals. Conclusions. This paper describes several primary issues that arise in the development of the phantomization radio image theory. The results obtained are the foundation for further research, which should be directed toward the development of mathematical models of the aerospace remote sensing system orbits, spatial and temporal signals emitted by the remote sensing radio systems from aerospace carriers, and formalization of the features of the underlying surface in the “SAR-PhR” system.